If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -16 + -3x + -16 = 0 Reorder the terms: -16 + -16 + -3x = 0 Combine like terms: -16 + -16 = -32 -32 + -3x = 0 Solving -32 + -3x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '32' to each side of the equation. -32 + 32 + -3x = 0 + 32 Combine like terms: -32 + 32 = 0 0 + -3x = 0 + 32 -3x = 0 + 32 Combine like terms: 0 + 32 = 32 -3x = 32 Divide each side by '-3'. x = -10.66666667 Simplifying x = -10.66666667
| -8x+4x-24=-28 | | 3-t/23+5=12 | | 4/3*(3.14)*1^3 | | 0.2-0.4x^2=-2 | | X^3-10X^2+34x=0 | | 7(a+4)=7(a-2) | | -7n-4+5=22 | | 4/3(3.14)1 | | f(x)=x^2-5x-14 | | 4x+8=2+20 | | 5(3+6x)-3=102 | | 31-12x=221 | | 4x^2+11x-25=0 | | 6x^2+11x-2x=0 | | 3/5k^2-10/3=0 | | 5x+4y=55 | | 15/x+3 | | 0.17y+0.04(y+4000)=1840 | | -4y+7=5y+2 | | (12.8)(4.1)= | | 0.01x+0.10x+0.25x(26-2x)=1.82 | | 7x^2-3x+0=0 | | 18-2p=3+p | | -x+3+10x=-2+4x+10 | | 3x+1=41 | | 31=4t+3 | | x-x^2-x^3=0 | | -x^2=-3x+5 | | 750-50*24= | | -11/t=8/48 | | -3p+8=6-(8p+5) | | 16(2x-4)=4(8x+9) |